Care-seeking correlates of acute respiratory illness among sheltered adults experiencing homelessness in Seattle, WA, 2019: a community-based cross-sectional study - Rogers, Julia H.; Hawes, Stephen E.; Wolf, Caitlin R.; Hughes, James P.; Englund, Janet A.; Starita, Lea M.; Chu, Helen Y. (Frontiers in Public Health, 2023)
Objective Multifarious barriers to accessing healthcare services among people experiencing homelessness (PEH) lead to delays in seeking care for acute infections, including those caused by respiratory viruses. PEH are at high risk of acute respiratory illness (ARI)-related complications, especially in shelter settings that may facilitate virus spread, yet data characterizing healthcare utilization for ARI episodes among sheltered PEH remained limited. Methods We conducted a cross-sectional study of viral respiratory infection among adult residents at two homeless shelters in Seattle, Washington between January and May 2019. We assessed factors associated with seeking medical care for ARI via self-report. We collected illness questionnaires and nasal swabs were tested for respiratory viruses by reverse transcription quantitative real-time PCR (RT-qPCR). Results We observed 825 encounters from 649 unique participants; 241 (29.2%) encounters reported seeking healthcare for their ARI episode. Seasonal influenza vaccine receipt (adjusted prevalence ratio [aPR] 1.39, 95% CI 1.02–1.88), having health insurance (aPR 2.77, 95% CI 1.27–6.02), chronic lung conditions (aPR 1.55, 95% CI 1.12-2.15), and experiencing influenza-like-illness symptoms (aPR 1.63, 95% CI 1.20 - 2.20) were associated with increased likelihood of seeking care. Smoking (aPR 0.65, 95% CI 0.45-0.92) was associated with decreased likelihood of seeking care. Discussion Findings suggest that care seeking for viral respiratory illness among PEH may be supported by prior engagement with primary healthcare services. Strategies to increase healthcare utilization may lead to earlier detection of respiratory viruses.